Gambaran anemia gizi dan kaitannya dengan asupan serta pola makan pada tenaga kerja wanita di Tangerang, Banteng - Suyardi, M. Arifin; Andriani, Ance; L. Priyatna, Benny (Jurnal Kedokteran YARSI, 2009)
Health and nutritional status of female workers are factors determining the quality of human resources in the future. A cross sectional study was done in shoes factory on cutting and trimming department in Tangerang district, Banten. This study was conducted to observe the nutritional enemia profile in this group employing questionaire, anthropometricmeasurement, physical and laboratory examination. The population was female workers. Subjects were chossen using inclusion criteria. A total of 125 persons were admitted in this study. Overall the prevalence of undernutrition was 23 (18.4%). Anemia was found in 78 (62.4%), consisted of 55 (44%) nutritional anemia and 23 (18.4%) unknown caused. Nutritional anemia were separated to iron deficiency anemia 44 (35.2%),B12 deficiency anemia 2 (1.6%), iron + B12 deficiency anemia 4 (3.2%), iron + folic acid deficiency anemia 2 (1.6%), B12 + folic acid deficiency anemia 2 (1.6%), iron + B12 + folic acid deficiency anemia 1 (0.8%). This study concluded that the nutritional anemia was related significantly (p<0.05) to inadequacy protein and iron intake was well as unpair food pattern. In the future, effort should be done to give adequate nutrients intake especially sources of protein, iron, folic acid and B12 vitamin.